1995
DOI: 10.1104/pp.107.4.1257
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Adenosine 5[prime]-Triphosphate-Energized Transport of Glutathione-S-Conjugates by Plant Vacuolar Membrane Vesicles

Abstract: By characterization of the uptake of glutathione-S-conjugates, principally dinitrophenyl-S-glutathione (DNP-CS), by vacuolar membrane vesicles, we demonstrate that a subset of energy-dependent transport processes in plants are not H+-coupled but instead are directly energized by MgATP. The most salient features of this transport pathway are: (a) its specific, obligate requirement for MgATP as energy source; (b) the necessity for hydrolysis of the y-phosphate of MgATP for uptake; (c) the insensitivity of uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
101
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 48 publications
12
101
0
1
Order By: Relevance
“…2A) amounts to an accumulation ratio of 60. This value is similar to that computed for S-(2,4-dinitrophenyl) glutathione (DNP-GS), a model MRPtype ABC transporter substrate, for the same membrane preparation (Li et al, 1995).…”
Section: Glucosylation Of 5-hydroxychlorsulfuron Is a Prerequisite Fosupporting
confidence: 80%
See 3 more Smart Citations
“…2A) amounts to an accumulation ratio of 60. This value is similar to that computed for S-(2,4-dinitrophenyl) glutathione (DNP-GS), a model MRPtype ABC transporter substrate, for the same membrane preparation (Li et al, 1995).…”
Section: Glucosylation Of 5-hydroxychlorsulfuron Is a Prerequisite Fosupporting
confidence: 80%
“…It has been reported that red beet vacuolar membrane vesicles, purified by the same procedure (Li et al, 1995), accumulate a glutathione conjugate of pHCA, a key intermediate in the phenylpropanoid pathway, and that conjugation is necessary for uptake (Walczak and Dean, 2000). In light of these findings, the likely involvement of an MRP-type transporter in uptake of the glutathione conjugate, and the fact that plants primarily glucosylate pHCA, we synthesized the phenolic glucoside of pHCA (pHCAG) to see if it also undergoes transport and, if so, whether it is subject to MRP-mediated or H ϩ -coupled transport.…”
Section: Uptake Of Glucosylated P-hydroxycinnamic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Taurocholate may act as a competitive inhibitor to BCECF in these experiments. Vanadate also inhibited the directly energized transporter that pumps these organic anions into barley aleurone vacuoles in a manner similar to that found for these transporters in other types of plant cells Li et al, 1995b;Coleman et al, 1997a). Consistent with its ability to inhibit anion transport, probenecid decreased the ATP-dependent uptake of BCECF into isolated vacuoles.…”
Section: Two Kinds Of Atp-dependent Transporters Load Fluorescent Prosupporting
confidence: 66%